An ordered mesoporous nanometer copper-iron-based oxide catalyst, a preparation method and application thereof

CN118454672BActive Publication Date: 2026-11-03MOUTAI INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311106659.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-30
Publication Date
2026-11-03
Estimated Expiration
2043-08-30

AI Technical Summary

Technical Problem

Existing Cu-M-based catalysts exhibit low ethanol selectivity during ethanol synthesis and struggle to effectively suppress the formation of methanol and hydrocarbon byproducts, resulting in high industrial production costs. Improving the contact area of ​​the active sites and the electronic synergistic effect of the catalysts is crucial.

Method used

By employing ordered mesoporous copper-iron-based oxide nanocatalysts, and constructing strongly interacting copper-iron bimetallic active interface centers, the catalyst's active centers are enhanced with high specific surface area and controlled pore size to adsorb reactant molecules, thereby controlling product transport and achieving highly selective catalytic syngas-directed synthesis of ethanol.

Benefits of technology

It improves the selectivity and space-time yield of ethanol, reduces the formation of methanol and hydrocarbon byproducts, and enhances the activity and stability of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118454672B_ABST
    Figure CN118454672B_ABST
Patent Text Reader

Abstract

The application discloses a kind of catalyst, especially relates to a kind of ordered mesoporous nano copper iron-based oxide catalyst, the salt solution of iron salt, aluminium salt, zirconium salt is filled into CMK-3 ordered mesoporous carbon pore channel, after drying and high-temperature calcination, ordered mesoporous metal oxide precursor is obtained;Copper salt solution is impregnated to the ordered mesoporous metal oxide precursor, after drying roasting, the ordered mesoporous nano copper iron-based oxide catalyst is obtained.Compared with traditional non-porous synthesis ethanol catalyst, the ordered mesoporous copper iron-based oxide catalyst of the application, not only constructs the copper iron bimetallic active interface center with strong interaction, enhances the synergistic effect of double active center, utilizes the high external specific surface area of ordered mesoporous, improves the adsorption reactant molecule capacity of double active center, simultaneously by regulating pore size and pore length, can control the rapid transport of product in hole, realizes high selectivity catalytic synthesis gas directional synthesis ethanol.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of catalyst and its preparation technology, and specifically relates to an ordered mesoporous nano-copper-iron based oxide catalyst, its preparation method and application. Background Technology

[0002] Ethanol has a wide range of applications, not only in the preparation of high-value-added fine chemicals but also as a direct vehicle fuel. The catalytic conversion of coal / biomass into ethanol via syngas gasification is a crucial pathway for achieving efficient and clean resource conversion. The direct catalytic synthesis of ethanol from syngas is a complex reaction involving multiple elementary reactions: adsorption of CO and H2 on the catalyst, bond dissociation (including CO and HH bonds), bond formation (including C / C and OH bonds), and intermediate generation. This process requires not only the dissociation and adsorption of CO followed by hydrogenation to form CH4 x Furthermore, CO must be adsorbed in molecular form and then inserted into C-C bonds, and the two must reach an appropriate ratio, which places high demands on the design and development of catalysts. Currently, catalyst systems mainly fall into four categories: noble metal Rh-based catalysts, modified methanol synthesis catalysts, Mo-based catalysts, and modified Fischer-Tropsch (FT) synthesis catalysts. Among them, modified FT synthesis catalysts involve adding transition metals or alkali metals to traditional FT synthesis catalysts to improve the selectivity and space-time yield of oxygen-containing compounds, especially alcohols.

[0003] It is generally believed that Cu serves as the active site for both non-dissociative adsorption of CO and dissociative adsorption of H2, while metals such as Fe and Co mainly promote the activated dissociation of CO and catalyze the growth of the CC chain. Currently, methods to improve the ethanol selectivity and space-time yield of Cu-M (M = Fe, Co)-based catalysts mainly involve finding suitable promoters (Zn, Mn, K, Cs) and supports (activated carbon, metal oxides, molecular sieves) to adjust the electronic state and surface / interface structure of the catalyst. Because the microstructural transformation behavior of Fe / Co-based catalysts in the CO hydrogenation reaction is quite complex, different oxides of Fe... x O y / Co x O y and carbide Fe x C yThe coexistence of Cu-M bimetallic components in the reaction makes it particularly difficult to regulate the synergistic effect between them. This results in the formation of a significant amount of methanol and hydrocarbon byproducts during ethanol synthesis, with ethanol selectivity below 60%. Therefore, effectively regulating the formation of more active interface structures in the Cu-M bimetallic catalyst to generate a strong electronic synergistic effect, increase the specific surface area of ​​the bimetallic catalyst, thereby increasing the contact area between the active center and reactant molecules, increasing the number of ethanol catalytic active sites on the catalyst surface, suppressing the formation of methanol and hydrocarbon byproducts, and improving the selectivity of ethanol products has become a key issue in Cu-M-based catalyst research. It is also an urgent requirement for reducing industrial production costs and saving energy.

[0004] In recent years, ordered mesoporous metal oxides have attracted significant attention in the field of catalysis due to their extremely high specific surface area, regular and ordered pore structure, narrow pore size distribution, continuously tunable pore size, and strong interactions between active centers. A study (Han Z., et al., Journal of Catalyst, 2021, 396:242-250) reported the synthesis of an ordered mesoporous ZnO-ZrO2 catalyst with controllable pore size using evaporation-induced self-assembly, which exhibited a higher specific surface area and larger pore size compared to co-precipitation-prepared catalysts, with the surface active components showing better catalytic performance for CO2 hydrogenation. A study (Gao J., et al., Journal of Colloid and Interface Science, 2018, 524:409-416) reported the synthesis of a catalyst with a large specific surface area (158 m²) using KIT-6 as a template. 2 .g -1 Three-dimensionally ordered mesoporous CuFe₂O₄ exhibits excellent performance in degrading sulfonamides. Ordered mesoporous metal oxides have shown great potential in catalytic oxidation and degradation of volatile organic compounds and catalytic conversion of NOx. However, the preparation of ordered mesoporous nano-copper-iron-based oxide catalysts for the catalytic directed synthesis of ethanol from syngas has not yet been reported in the literature. Summary of the Invention

[0005] The purpose of this invention is to provide a highly selective and stable ordered mesoporous copper-iron-based oxide catalyst, its preparation method, and its application.

[0006] The present invention discloses an ordered mesoporous nano-copper-iron-based oxide catalyst, wherein a salt solution of iron salt, aluminum salt, and zirconium salt is poured into the ordered mesoporous carbon channels of CMK-3, and after drying and high-temperature calcination, an ordered mesoporous metal oxide precursor is obtained; a copper salt solution is impregnated onto the ordered mesoporous metal oxide precursor, and after drying and calcination, the ordered mesoporous nano-copper-iron-based oxide catalyst is obtained.

[0007] Furthermore, the molar composition of the copper, iron, aluminum, and zirconium in the catalyst, based on the metal elements, is Cu 30%–45%, Fe 35%–50%, Al 2%–20%, and Zr 1%–10%.

[0008] Furthermore, the iron salt is one or more of ferric nitrate, ferric acetate, ferric chloride, and ferric sulfate.

[0009] Furthermore, the aluminum salt is one or more of aluminum nitrate, aluminum acetate, aluminum chloride, and aluminum sulfate.

[0010] Furthermore, the zirconium salt is one or more of zirconium nitrate, zirconium acetate, zirconium chloride, and zirconium sulfate.

[0011] Furthermore, the copper salt is one or more of copper nitrate, copper acetate, copper chloride, copper sulfate, and copper oxalate.

[0012] Furthermore, the catalyst has a pore diameter of 3–8 nm and a specific surface area of ​​200–500 m². 2 / g.

[0013] The present invention discloses a method for preparing an ordered mesoporous nano-copper-iron-based oxide catalyst, comprising dissolving iron salt, aluminum salt, and zirconium salt together in an ethanol solvent, stirring until the solution is clear and transparent, adding CMK-3 ordered mesoporous carbon as a template agent and stirring until the solvent evaporates to dryness; then calcining at 500-800℃ for 3-6 hours to obtain an ordered mesoporous metal oxide precursor; impregnating the ordered mesoporous metal oxide precursor with a copper salt solution, stirring for 3-8 hours, drying at 60-100℃, and calcining at 300-450℃ for 1-4 hours to obtain the ordered mesoporous nano-copper-iron-based oxide catalyst.

[0014] Furthermore, the total mass ratio of the iron salt, aluminum salt, and zirconium salt to the CMK-3 template is 0.1 to 10:0.3.

[0015] This invention relates to the application of an ordered mesoporous copper-iron-based oxide catalyst in the ethanol synthesis process. The reduction conditions for the ordered mesoporous copper-iron-based oxide catalyst are as follows: reduction at a reducing gas composition of H2 / N2 volume ratio of 1–2:10 and a reduction temperature of 200–300℃ for 6–12 h; the reduced catalyst is then subjected to a reaction at a temperature of 240–320℃, a reaction pressure of 3–6 MPa, a reactant composition of (H2-CO2) / (CO+CO2) molar ratio of 1.5–3.5, and a space velocity of 2000–20000 L / (kg⁻¹). cat﹒ The synthesis of ethanol from syngas was carried out under the conditions of h).

[0016] The technical advantages of this invention are as follows:

[0017] Compared with traditional non-porous ethanol synthesis catalysts, the ordered mesoporous copper-iron-based oxide catalyst of the present invention not only constructs copper-iron bimetallic active interface centers with strong interactions, enhancing the synergistic effect of the two active centers, but also utilizes the high external specific surface area of ​​the ordered mesopores to improve the adsorption capacity of the two active centers for reactant molecules. At the same time, by adjusting the pore size and channel length, the rapid transport of products within the pores can be controlled, achieving highly selective catalytic syngas-directed synthesis of ethanol. Attached Figure Description

[0018] Figure 1 This is a transmission electron microscope image of the ordered mesoporous nano-copper-iron-based oxide catalyst prepared in Example 1 of the present invention.

[0019] Figure 2 This is a particle size distribution chart of copper nanoparticles in Example 1 of the present invention. Detailed Implementation

[0020] The following detailed description illustrates the specific implementation method:

[0021] Example 1: A method for preparing an ordered mesoporous nano-copper-iron based oxide catalyst, comprising the following steps:

[0022] (1) Preparation of precursor solution: Dissolve ferric nitrate, aluminum acetate and zirconium chloride together in ethanol solvent and stir until the solution is clear and transparent;

[0023] (2) Use 3g of CMK-3 ordered mesoporous carbon as a template agent and mix it with the precursor liquid (total mass of precursor salt is 10g) until the solvent evaporates to dryness;

[0024] (3) The sample obtained in step (2) was calcined in air at 650°C for 4 hours and then cooled to room temperature to obtain an ordered mesoporous metal oxide precursor.

[0025] (4) Immerse the sample from step (3) in copper acetate solution, stir the mixed solution for 6 hours, and dry at 80°C;

[0026] (5) The sample obtained in step (4) was calcined at 350℃ for 2 h to obtain an ordered mesoporous nano-copper-iron-based oxide catalyst. The molar ratio of the metal elements was Cu:Fe:Al:Zr = 37.3:43.5:13.6:5.6.

[0027] from Figure 1 It can be seen that copper species are uniformly dispersed in the interconnected, ordered mesoporous channels composed of iron, aluminum, and zirconium oxides. Figure 2 It can be seen that the average particle size of copper species is 3.1 nm.

[0028] The reduction and reaction process conditions for the catalyst prepared in this invention are as follows: reduction for 8 hours at a reducing gas composition of H2 / N2 volume ratio of 1:10 and a reduction temperature of 260℃; then switching to the feed gas with a (H2-CO2) / (CO+CO2) molar ratio of 2.0, at a reaction temperature of 280℃, a reaction pressure of 5.0 MPa, and a space velocity of 12000 L / (kg⁻¹). cat﹒ The reaction was carried out under the following conditions: CO conversion was 75%, total alcohol selectivity was 41%, ethanol molar fraction in total alcohol was 67%, and ethanol space-time yield was 232 g / (kg). cat﹒ h).

[0029] Example 2: A method for preparing an ordered mesoporous nano-copper-iron based oxide catalyst, comprising the following steps:

[0030] (1) Preparation of precursor solution: Dissolve ferric acetate, aluminum nitrate and zirconium nitrate together in ethanol solvent and stir until the solution is clear and transparent;

[0031] (2) Use 3g of CMK-3 ordered mesoporous carbon as a template agent and mix it with the precursor liquid (total mass of precursor salt is 30g) until the solvent evaporates to dryness;

[0032] (3) The sample obtained in step (2) was calcined in air at 750°C for 3 hours and then cooled to room temperature to obtain an ordered mesoporous metal oxide precursor.

[0033] (4) Immerse the sample from step (3) in copper acetate solution, stir the mixed solution for 4 hours, and dry at 100°C.

[0034] (5) The sample obtained in step (4) was calcined at 400℃ for 2.5 h to obtain an ordered mesoporous nano-copper-iron-based oxide catalyst. The molar ratio of the metal elements was Cu:Fe:Al:Zr = 41.2:40.3:16.5:2.0.

[0035] The reduction and reaction process conditions for the catalyst prepared in this invention are as follows: reduction for 12 h at a reducing gas composition of H2 / N2 volume ratio of 2:10 and a reduction temperature of 280℃; then switching to the feed gas with a (H2-CO2) / (CO+CO2) molar ratio of 3.0, at a reaction temperature of 300℃, a reaction pressure of 4.5 MPa, and a space velocity of 16000 L / (kg⁻¹). cat﹒ The reaction was carried out under the following conditions (h). The CO conversion rate was 62%, the total alcohol selectivity was 47%, the molar fraction of ethanol in the total alcohol was 72%, and the space-time yield of ethanol was 277 g / (kg). cat﹒ h).

[0036] Example 3: A method for preparing an ordered mesoporous nano-copper-iron based oxide catalyst, comprising the following steps:

[0037] (1) Preparation of precursor solution: Dissolve ferric chloride, aluminum sulfate and zirconium acetate together in ethanol solvent and stir until the solution is clear and transparent;

[0038] (2) Use 3g of CMK-3 ordered mesoporous carbon as a template agent and mix it with the precursor liquid (total mass of precursor salt is 60g) until the solvent evaporates to dryness;

[0039] (3) The sample obtained in step (2) was calcined in air at 700°C for 3.5 h and then cooled to room temperature to obtain an ordered mesoporous metal oxide precursor.

[0040] (4) Immerse the sample from step (3) in copper acetate solution, stir the mixed solution for 8 hours, and dry at 60°C.

[0041] (5) The sample obtained in step (4) was calcined at 300℃ for 4 h to obtain an ordered mesoporous nano-copper-iron-based oxide catalyst. The molar ratio of the metal elements was Cu:Fe:Al:Zr = 32.7:46.8:11.6:8.9.

[0042] The reduction and reaction process conditions of the catalyst prepared in this invention are as follows: reduction for 7 h at a reducing gas composition of H2 / N2 volume ratio of 3.5:10 and a reduction temperature of 300℃; then switching to the feed gas with a (H2-CO2) / (CO+CO2) molar ratio of 1.5, at a reaction temperature of 320℃, a reaction pressure of 6.0 MPa, and a space velocity of 20000 L / (kg⁻¹). cat﹒ The reaction was carried out under h) conditions. The CO conversion rate was 57%, the total alcohol selectivity was 52%, the molar fraction of ethanol in the total alcohol was 76%, and the space-time yield of ethanol was 305 g / (kg). cat﹒ h).

[0043] Example 4: A method for preparing an ordered mesoporous nano-copper-iron based oxide catalyst, comprising the following steps:

[0044] (1) Preparation of precursor solution: Dissolve ferric sulfate, aluminum sulfate and zirconium nitrate together in ethanol solvent and stir until the solution is clear and transparent;

[0045] (2) Use 3g of CMK-3 ordered mesoporous carbon as a template agent and mix it with the precursor liquid (total mass of precursor salt is 5g) until the solvent evaporates to dryness;

[0046] (3) The sample obtained in step (2) was calcined in air at 550°C for 6 hours and then cooled to room temperature to obtain an ordered mesoporous metal oxide precursor.

[0047] (4) Immerse the sample from step (3) in copper acetate solution, stir the mixed solution for 6 hours, and dry at 70°C.

[0048] (5) The sample obtained in step (4) was calcined at 450℃ for 2 h to obtain an ordered mesoporous nano-copper-iron-based oxide catalyst. The molar ratio of the metal elements was Cu:Fe:Al:Zr = 44.2:36.5:12.0:7.3.

[0049] The reduction and reaction process conditions for the catalyst prepared in this invention are as follows: reduction is carried out for 10 hours at a reducing gas composition of H2 / N2 volume ratio of 1:10 and a reduction temperature of 230℃; then the feed gas is switched to a composition of (H2-CO2) / (CO+CO2) molar ratio of 1.5, and the reaction is carried out at a reaction temperature of 250℃, a reaction pressure of 4.0 MPa, and a space velocity of 5000 L / (kg⁻¹). cat﹒ The reaction was carried out under the following conditions: CO conversion was 72%, total alcohol selectivity was 37%, ethanol molar fraction in total alcohol was 62%, and ethanol space-time yield was 207 g / (kg). cat﹒ h).

Claims

1. An ordered mesoporous nano-copper-iron based oxide catalyst, characterized in that: The catalyst is prepared by injecting a salt solution of iron salt, aluminum salt, and zirconium salt into the ordered mesoporous carbon channels of CMK-3, followed by drying and high-temperature calcination to obtain an ordered mesoporous metal oxide precursor. The ordered mesoporous metal oxide precursor was impregnated with a copper salt solution and then dried and calcined to obtain the ordered mesoporous nano-copper-iron-based oxide catalyst.

2. The ordered mesoporous nano-copper-iron based oxide catalyst according to claim 1, characterized in that: The catalyst contains copper, iron, aluminum, and zirconium, with the following molar composition based on metallic elements: Cu 30%–45%, Fe 35%–50%, Al 2%–20%, and Zr 1%–10%.

3. The ordered mesoporous nano-copper-iron based oxide catalyst according to claim 1, characterized in that: The iron salt is one or more of ferric nitrate, ferric acetate, ferric chloride, and ferric sulfate.

4. The ordered mesoporous nano-copper-iron based oxide catalyst according to claim 1, characterized in that: The aluminum salt is one or more of aluminum nitrate, aluminum acetate, aluminum chloride, and aluminum sulfate.

5. The ordered mesoporous nano-copper-iron based oxide catalyst according to claim 1, characterized in that: The zirconium salt is one or more of zirconium nitrate, zirconium acetate, zirconium chloride, and zirconium sulfate.

6. The ordered mesoporous nano-copper-iron based oxide catalyst according to claim 1, characterized in that: The copper salt is one or more of copper nitrate, copper acetate, copper chloride, copper sulfate, and copper oxalate.

7. The ordered mesoporous nano-copper-iron based oxide catalyst according to claim 1, characterized in that: The catalyst has a pore diameter of 3–8 nm and a specific surface area of ​​200–500 m². 2 / g.

8. A method for preparing an ordered mesoporous nano-copper-iron based oxide catalyst according to any one of claims 1 to 7, characterized in that: Iron, aluminum, and zirconium salts were dissolved together in ethanol solvent and stirred until the solution was clear and transparent. CMK-3 ordered mesoporous carbon was added as a template agent and stirred until the solvent evaporated to dryness. Then, it was calcined at 500-800℃ for 3-6 hours to obtain an ordered mesoporous metal oxide precursor. A copper salt solution was impregnated onto the ordered mesoporous metal oxide precursor, stirred for 3-8 hours, dried at 60-100℃, and calcined at 300-450℃ for 1-4 hours to obtain the ordered mesoporous nano-copper-iron based oxide catalyst.

9. The method for preparing an ordered mesoporous nano-copper-iron based oxide catalyst according to claim 8, characterized in that: The total mass ratio of the iron salt, aluminum salt, and zirconium salt to the CMK-3 template is 0.1 to 10:0.

3.

10. The application of an ordered mesoporous nano-copper-iron based oxide catalyst according to any one of claims 1 to 7 in the ethanol synthesis process, characterized in that: The reduction process conditions for the ordered mesoporous nano-copper-iron based oxide catalyst are as follows: reduction at a reducing gas composition of H2 / N2 volume ratio of 1–2:10 and a reduction temperature of 200–300℃ for 6–12 h; the reduced catalyst is then subjected to a reaction at a temperature of 240–320℃, a reaction pressure of 3–6 MPa, a reactant composition of (H2-CO2) / (CO+CO2) molar ratio of 1.5–3.5, and a space velocity of 2000–20000 L / (kg⁻¹). cat﹒ The synthesis of ethanol from syngas was carried out under the conditions of h).